Coup-TFII expression defines two different septum transversum cell compartments crucial to cardiac septation and compact ventricular wall growth - Guadix-Domínguez, Juan Antonio; Pires-Gomes, Adriana; Cano-Ballesteros, Sara; Pogontke, Cristina; Palmquist-Gomes, Paul; Rojas, Anabel; Pérez-Pomares, José María (My University, 2018)
COUP-TFII encodes for an orphan nuclear receptor expressed by multiple embryonic tissues. COUP-TFII functions include the regulation of mesodermal progenitor differentiation and cell fate specification, and is required for completion of cardiovascular development as shown by the early death (E9.5) of COUP-TFII-null mice. In this study, we show that COUP-TFII, which is strongly expressed in the atrial myocardium, is also expressed in two different compartments of the septum transversum (ST, E9.5), a mesodermal folding adjacent to cardiac inflow myocardium. The first ST compartment is COUP-TFII+/Isl1+; cells in this compartment concentrate in the posterior part of the ST, overlap with SHF, and are continuous with the dorsal mesenchymal protrusion (DMP, also known as spina vestibuli). The second compartment is characteristically COUP-TFII+/Isl1-, and comprises the majority of proepicardial cells. To dissect the role of COUP-TFII+ ST cells in cardiac development, we conditionally deleted COUP-TFII in the ST using two different Cre constructs (Wt1Cre; G2-Gata4Cre). We show that COUP-TFII deletion in the ST is most severe in G2-Gata4Cre;COUP-TFII-/- mice, containing various cardiovascular progenitor lineages. Mutant mice display atrial septation and atrioventricular septal defects as well as a severe disruption of compact ventricular myocardial growth and coronary vascularization. We conclude that COUP-TFII plays critical, pleiotropic, tissue-dependent roles during cardiac septation, growth and vascularization.
Keywords: Sistema Cardiovascular; Cardiovascular develpment (Desarrollo Cardiovascular)